Dentinogenesis imperfecta type 1-Shield’s classification (1973): a rare case report and literature review - Gopal, Saraswathi K.; V., Poongodi; S., Priyadharshini (International Journal of Research in Medical Sciences, 2023)
Dentinogenesis imperfecta (DI) is an autosomal dominant disorder that affects the dentin development. It is characterized by the presence of opalescent dentin, with dusky blue to brownish discoloration of the teeth. This condition is genetically and clinically heterogeneous; DI may affect only the teeth or it may be associated with the osteogenesis imperfect (OI). When both are associated there are various degrees of clinical presentation from mild form with less significant signs to severe form such as death in infancy. The most familiar classification system of this hereditary disorder is Shields classification which is of 3 types namely, type I, DI associated with OI, type II is not associated with OI. Type III which is also known as ‘Brandywine type’ DI. This case report describes a rare case of 32-year-old female patient who showed the characteristic features of Shield’s classification type I with penetrance of defect through 4 generations.